New insights on severe clinical manifestations and deaths from visceral leishmaniasis in free-living crab-eating foxes (Cerdocyon thous) in Brazil (Research, Society and Development, 2021)
Visceral leishmaniasis (VL) is a zoonotic and severe neglected tropical disease, with worldwide distribution, that still cause many deaths among dogs and humans. Brazil is the country responsible for about 97% of the cases of leishmaniasis in the Americas and the disease is still considered a serious public health concern. Among wild mammalians, studies demonstrate the involvement of Cerdocyon thous in the biological cycle of Leishmania. Nevertheless, several authors consider the clinical manifestation of the disease to be rare or mild in free-living animals. Herein, we demonstrate the occurrence of severe clinical sings and deaths caused by VL in free-living crab-eating foxes. Three specimens of foxes collected from periurban areas were diagnosed with VL. The animals presented cutaneous, ophthalmological, gastrointestinal, locomotor and hematological alterations, and died after clinical progression. We identified the presence of anti-Leishmania antibodies by immunochromatographic test in all specimens. We also observed intra and extracellular amastigotes in skin cytology and lymph node aspirate. Furthermore, Leishmania infantum DNA was identified in all samples by the polymer chain reaction technique. Additionally, we performed blood count and stool parasitological tests and observed hematological disorders common to VL, such as anemia and lymphopenia. Taken together, our data demonstrate that VL can induce clinical complications and even cause death in C. thous and corroborate that this crab-eating fox is an adequate host for L. infantum.